2022
DOI: 10.3389/fpsyt.2022.937511
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction and Suicidal Ideation Among Chinese College Students During the Recurrent Outbreak of COVID-19: A Moderated Mediation Model

Abstract: The present study examined a moderated mediation model between life satisfaction and suicidal ideation among Chinese college students during the recurrent outbreak of COVID-19. Seven hundred and ninety college students participated in the study and completed questionnaires on life satisfaction, suicidal ideation, depression, and gratitude. Findings indicated that (1) Depression played a partial mediating role between life satisfaction and suicidal ideation. Life satisfaction was not only directly affected suic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…It can easily lead to suicidal intentions. 35 Therefore, the education department should be more explicit about the root causes of college students’ psychological problems and find corresponding solutions. Secondly, this study found that in terms of gender, male college students are more likely to have more suicidal tendencies than female college students, which may be because males have relatively fewer emotional expression channels and are less likely to resolve negative psychological tendencies.…”
Section: Discussionmentioning
confidence: 99%
“…It can easily lead to suicidal intentions. 35 Therefore, the education department should be more explicit about the root causes of college students’ psychological problems and find corresponding solutions. Secondly, this study found that in terms of gender, male college students are more likely to have more suicidal tendencies than female college students, which may be because males have relatively fewer emotional expression channels and are less likely to resolve negative psychological tendencies.…”
Section: Discussionmentioning
confidence: 99%
“…Although reflective rumination and positive coping are proven to be significantly related to PTG, it is difficult to find research linking the three variables related to PTG in the context of the COVID-19 epidemic. The protective factor model suggests that the interaction between two protective factors can enhance the results (Fergus & Zimmerman, 2005;Yu et al, 2022). Prior research has demonstrated that active coping is associated with lower depressive symptoms, and the magnitude of this association is strongest among people with high reflective rumination (Marroquín et al, 2010).…”
Section: Reflective Rumination As Moderatormentioning
confidence: 99%
“…Depression, anxiety, and stress, paired with perceived burdensomeness and thwarted belongingness, may further affect individuals' wellbeing (40). Improving a sense of perceived burdensomeness and thwarted belongingness may improve SWL and result in lower suicidal risks (41)(42)(43). By building on the above understanding, we investigate the degrees to which thwarted belongingness and perceived burdensomeness alter the relationship between depression, anxiety, and stress and SWL.…”
Section: The Theory and Role Of Interpersonal Needs As The Moderating...mentioning
confidence: 99%